2016
DOI: 10.1111/1752-1688.12395
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Assessment of Runoff Nitrogen from Turf, Forest, Meadow, and Mixed Landuse Watersheds

Abstract: Landscaping paradigms that encourage high-input, intensively managed and mono-culture turf/ lawn landscapes have raised concerns about water quality. We conducted a watershed-scale assessment of landscaping practices that included turf, urban, forest, native meadow, and mixed landuse watersheds with a professional golf course and a parking lot. The turf site was moderately managed and had lower fertilizer inputs than those typically used by homeowners and golf courses. Stream water sampling was performed durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…Further, under the same rainfall intensity, the aeolian sandy soil is more likely to erode than other soil types, and for the higher the slope (>15 • ), it is easier to produce runoff and erosion, which provides an important carrier for nitrogen. Finally, there is a significant negative correlation between the nitrogen load intensity and the forest area ratio; this result is consistent with the results found by Bachman et al [75]. As the forest land in the Chaohe River basin has been dominated by woody plants for many years, and many dwarf shrubs can cover the surface, these plants can retain more nitrogen and protect nutrients from runoff.…”
Section: Identification Of Key Impact Factorssupporting
confidence: 91%
“…Further, under the same rainfall intensity, the aeolian sandy soil is more likely to erode than other soil types, and for the higher the slope (>15 • ), it is easier to produce runoff and erosion, which provides an important carrier for nitrogen. Finally, there is a significant negative correlation between the nitrogen load intensity and the forest area ratio; this result is consistent with the results found by Bachman et al [75]. As the forest land in the Chaohe River basin has been dominated by woody plants for many years, and many dwarf shrubs can cover the surface, these plants can retain more nitrogen and protect nutrients from runoff.…”
Section: Identification Of Key Impact Factorssupporting
confidence: 91%
“…While we did observe clear evidence that land conversion to residential lawns accelerates N cycling in cities across the United States, we did not observe changes in potential net N mineralization and microbial biomass N content, and we did not observe any effects of self-reported fertilizer input on N cycling. These results were consistent with previous studies in BAL (Groffman et al, 2009;Raciti et al, 2008; and elsewhere (Bachman et al, 2016;Bock & Easton, 2020;Hall et al, 2009;Herrmann & Cadenasso, 2017;Wang et al, 2014) that find limited differences in soil N cycling processes between fertilized and unfertilized lawns. This outcome may be because our measure of fertilizer use here (self-reported in a telephone survey) was not quantitative or time-specific.…”
Section: Soil Nitrogen Cyclingsupporting
confidence: 93%
“…Evaluating the effects of lawn management practices on biogeochemical variables has been challenging because although controlled field and laboratory studies have shown how fertilizer use on lawns creates clear risks for water and air pollution (Morton et al, 1988), studies of lawns managed by homeowners show variations in fertilizer applications (Fraser et al, 2013), mixed evidence for environmental effects (Bachman et al, 2016;Bock & Easton, 2020;Carey et al, 2012;Groffman et al, 2009;Petrovic, 1990), and that the behaviors that drive this soil variability are complex and multi-scale (Campbell et al, 2014;Harris et al, 2012Harris et al, , 2013Hayden et al, 2015;Larson et al, 2020;Locke et al, 2018;Martini et al, 2013Martini et al, , 2014Polsky et al, 2014;Sisser et al, 2016).…”
Section: The Importance Of Managementmentioning
confidence: 99%
“…However, as rainfall increased, the amount of carbon runoff increased. How the amount of carbon flux changed in relation to the land cover type and land management by watershed and how it affected water quality was examined [12]. Finally, 34 years' worth of nutrient circulation patterns in a Eucalyptus forest were analyzed, and it was determined that differences in species were the key variable regarding the change in nutrient patterns [13].…”
Section: Introductionmentioning
confidence: 99%